The Use of Ruang Siswa on Students' Motivation to Learn Islamic Religious Education - M Musaeri (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Learning motivation is an important requirement that students must have in learning activities, especially learning amid the Covid-19 pandemic which is carried out remotely using various supporting media. The aim of the research is to know the response of the use of ‘Ruang Siswa’ to the students’ learning motivation on Islamic religious education subject. The method of the research is qualitative-descriptive. The data collection technique is an online response questionnaire by using google form. The research was done in SDIT Nurul Iman Purwantoro, Wonogiri on the first semester in 2021/2022. The research sample is 100 students of totally 194 students (8 classes , grade 4 to 6). The sampling technique is using random sampling. Based on the research done, the result is approximately 97% for consentration imdicator, 83% for curiosity indicator, 90% for spirit indicator, 86% for readiness indicator, 86% for enthusiast indicator, 95% for unyielding indicator, 85% for confidence indicator, 84% for independence indicator. Overall the learning motivation indicator is high so it can be concluded that the use of “Ruang Siswa” giving effect for motivation learning of the Islamic religious education subject is good based on the percentage result of each learning motivation indicators. Hopefully in the future “Ruang Siswa” could facilitate and improve the students’ learning motivation optimally.